Improvement of Subjects Understanding Development of Teaching Materials Through Project Based Learning - Megasari, Rizza; Dwi Putri, Rizky; Rachmawati, Dian (KnE Social Sciences, 2020)
The course for developing teaching materials is a subject that must be taken by educational students. Students as prospective teachers must be able to make good quality teaching materials so that learning can run effectively and efficiently. In the course of developing instructional materials, students are required to be able to produce a print teaching material that is appropriate for use by students. Teaching materials can be said to be of good quality and appropriate if it is in accordance with the learning objectives that must be achieved by students. This research is a descriptive study with an analysis of teaching materials that have been developed by students through project-based learning. The results of the study can be seen that the quality of teaching materials that have been developed along with the cognitive abilities of students master the material of teaching material development subjects. Good quality teaching materials indicate mastery in cognitive abilities as well. Keywords: development, teaching material, project-based learning